The Influence of Product Quality on Repurchase Intention of Holland Bakery With Customer Satisfaction as an Intervening Variable - Rosdianti, Syahfani Eka; Firdaus , Firdaus (Economics and Business International Conference Proceeding, 2024)
This research aims to analyze and determine the influence of product quality on repurchase intentions with customer satisfaction as a mediating variable. The research method used in this research uses a quantitative approach. The population in this study were Holland Bakery Kedungmundu Semarang customers. The sample in this study amounted to 121 respondents. Results of research data analysis using PLS-SEM (Partial Least Square - Structural Equation Modeling) with SmartPLS 3.0 software. The research results show that product quality has a positive and significant effect on customer satisfaction, product quality has a positive and significant effect on repurchase intention, customer satisfaction has a positive and significant effect on repurchase intention, and customer satisfaction mediates the relationship between product quality and repurchase intention.